2023
DOI: 10.1002/hbm.26322
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of diffusion‐tensor and correlated diffusion imaging for studying white‐matter microstructural abnormalities: Application in COVID‐19

Abstract: There has been growing attention on the effect of COVID‐19 on white‐matter microstructure, especially among those that self‐isolated after being infected. There is also immense scientific interest and potential clinical utility to evaluate the sensitivity of single‐shell diffusion magnetic resonance imaging (MRI) methods for detecting such effects. In this work, the performances of three single‐shell‐compatible diffusion MRI modeling methods are compared for detecting the effect of COVID‐19, including diffusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…5 ). Other DTI measures have further supported less restricted diffusion, including increased extracellular free water ( Petersen et al, 2023 , Huang et al, 2023 ) and correlated diffusion imaging ( Teller et al, 2023 ). However, Teller et al ( Teller et al, 2023 ) reported more restricted diffusion in the cerebellum.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…5 ). Other DTI measures have further supported less restricted diffusion, including increased extracellular free water ( Petersen et al, 2023 , Huang et al, 2023 ) and correlated diffusion imaging ( Teller et al, 2023 ). However, Teller et al ( Teller et al, 2023 ) reported more restricted diffusion in the cerebellum.…”
Section: Resultsmentioning
confidence: 97%
“…Other DTI measures have further supported less restricted diffusion, including increased extracellular free water ( Petersen et al, 2023 , Huang et al, 2023 ) and correlated diffusion imaging ( Teller et al, 2023 ). However, Teller et al ( Teller et al, 2023 ) reported more restricted diffusion in the cerebellum. Furthermore, axonal injury and less coherent orientation of axons have been reported, as indicated by lower AD ( Planchuelo-Gómez et al, 2023 , Díez-Cirarda et al, 2022 ), lower fiber density ( Bispo et al, 2022 , Lathouwers et al, 2023 ), and lower volume fraction of intracellular water ( Huang et al, 2022 ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation